Microfinance Institutions and Growth of Small and Medium Enterprises in Mukono - Nathan Egaru (Uganda Christian University, 2025)
This study examined the role of Microfinance Institutions in fostering the growth of Small and Medium Enterprises within Mukono District, the study was motivated by the recognition that SMEs are critical drivers of economic development and employment yet their development and expansion is frequently constrained by limited access to financial services. Employing a descriptive case study of Mukono, data was collected through structured questionnaires and interviews made to a purposively sampled population comprising of SME owners, MFI managers and financial experts. A total of 52 respondents participated in the study providing insights into the dynamics of microfinance access, financial literacy and SME performance. The analysis revealed that microfinance services significantly influenced SME growth by providing vital capital that facilitates in investment in technology, human resource and market expansion. The findings showed that access to microfinance loans positively impacted revenue, employment, investment and overall business sustainability among SMEs. However, the study identified key challenges faced by SMEs including high interest rates, collateral requirements, limited financial literacy, complex loan application procedures and inadequate loan sizes. The research further explored the impact of financial literacy programs offered by MFIs which were found to enhance SMEs financial management skills, decision making and ability to access credit, that contribute improved business performance. The study also discussed internal audit aspects and challenges internal auditors encountered regarding transparency and accountability, emphasizing the importance of effective governance. Based on these findings, the research concluded that MFIs play a crucial role in supporting SME growth in Mukono, even with limitations posed by operational challenges and borrower related issues. The study recommended that microfinance modify their financial products to meet SME needs, simplify loan procedures, reduce collateral barriers and strengthen financial literacy initiatives to maximize their developmental impact. Overall the research contributed to understanding how microfinance facilitates SME development in Uganda’s semi urban context and provided policy insights for enhancing microfinance outreach and effectiveness in fostering sustainable enterprise growth.
Undergraduate